36=3y-3

Simple and best practice solution for 36=3y-3 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 36=3y-3 equation:


Simplifying
36 = 3y + -3

Reorder the terms:
36 = -3 + 3y

Solving
36 = -3 + 3y

Solving for variable 'y'.

Move all terms containing y to the left, all other terms to the right.

Add '-3y' to each side of the equation.
36 + -3y = -3 + 3y + -3y

Combine like terms: 3y + -3y = 0
36 + -3y = -3 + 0
36 + -3y = -3

Add '-36' to each side of the equation.
36 + -36 + -3y = -3 + -36

Combine like terms: 36 + -36 = 0
0 + -3y = -3 + -36
-3y = -3 + -36

Combine like terms: -3 + -36 = -39
-3y = -39

Divide each side by '-3'.
y = 13

Simplifying
y = 13

See similar equations:

| 16t^2+12t+4= | | cos^2(x)-2cos(x)+1=0 | | 4(7x^2+4x-6)=0 | | 0.2(0.1x+0.3)=-.06 | | 7-3(x+2)=1 | | 27-5x=11-7x | | cos(4X+1)=3*sin(2X) | | 7n-10=-12h-66 | | A=10-A | | 4x+9=-31-6x | | 3x-20y=17 | | 6/4/5.11/17/25 | | 8x+13y+4=47 | | (19b-4)-6(3b+2)=-3 | | [x]+[4x]=[2x]+[3x] | | 3x-1=1x+3 | | f(x+3)=5x-9 | | 6x+4x+2+7=6x+3+3x | | 1x+12x=-65+x | | (36^1/2-5^2) | | 12x^2+4x-1= | | 2x-20=x+10 | | (36^1/2-5^2)*81^1/2 | | 5x^2-13x+7=0 | | (36^1/2-52)*81^1/2 | | -2(u-6)=(3u+17) | | 9+y^2=0 | | 9x-6+6x-1=180 | | 3(2x+4)-2(4+5x)= | | 1-y^2=10 | | -5u+32=-7(u-2) | | 1/6(2x-5)=8 |

Equations solver categories